Development of Cognitive Assessment Instruments Based on Scientific Literacy on the Material of Chemical Equilibrium - Sukardi, Ekwan; Solikhin, Febrian; Wiwit, Wiwit (Jurnal Zarah, 2025)
This research is research and development (R&D) to produced valid and reliable scientific literacy based cognitive assessment instrument. An assessment instrument was developed to measure students' scientific literacy abilities on equilibrium material. This research aims to described the feasibility of the instrument in terms of expert validation, described the validity and reliability of the instrument in terms of empirical validation and described the scientific literacy abilities of class XI MIPA 5 students at SMA Negeri 4 Bengkulu City. The development model used in this research is the ADDIE model. The data in this research collected used a instruments needs questionnaire, validation sheet and product trial sheet. The subjects of this research were 184 from 3 different schools as validation subjects and 29 grade 11 MIPA 5 students at SMA Negeri 4 Bengkulu City for the 2023/2024 academic year as implementation subjects. The number of questions developed on this instrument is 23 multiple choice questions and 10 essays. The results of this research were: (1.) The expert feasibility assessment produced 21 multiple choice questions and 10 essay items worthy of being tested. (2.) The results of the empirical validity analysis using Rasch modeling with the help of the Winsteps program obtained 15 multiple choice questions and 9 valid essay questions. (3.) The results of the instrument reliability test obtained a Cronbach alpha of 0.92 or in the excellent category for multiple choice and 0.80 or in the good category for essays. (4.) The scientific literacy abilities of class XI MIPA 5 students were obtained by 6 students in the quite satisfactory category and 1 student in the satisfactory category.